Management Of Shallow Gas Kick At Syh-05 Well In West Java Area - Sandy Candra Yudha Halilintar; KRT Nur Suhascaryo; AM Suranto (Journal of Petroleum and Geothermal Technology, 2022)
SYH-05 Well Drilling Operation West Java Area, was planned to be drilled with a final depth of 1694.65 mMD / 1500 mbpl by directional well drilling. Drilling hazards on the 17½” trajectory were shallow gas, gumbo, and bit balling. Furthermore, on this trajectory, shallow gas handling and optimization of drilling were going to be executed through shallow gas kick countermeasures in the SYH-05 Well. The high gas readings from the SYH-03 Well and the SYH-04 Well are 867 units and 1275 units, respectively, at a depth of 500-520 mMD intervals.After carrying out mitigation for shallow gas mitigation, the SYH-05 Well would use a higher Mud Weight than the reference well in this study starting with MW 1.12 SG while the reference well started with MW 1.08 SG, and the use of Annular – Single Ram 21-1/ 4” 2K with 10” Ball Valve as Diverter System. Moreover, to overcome the Kick Volume which was larger than the 17-1/2” hole, a 12-1/4” Pilot Hole would be installed. Prepare High Density Mud as a Contingency Plan and 4 Mud Pumps to anticipate the implementation of High Flow Rate Dynamic Kill. In the Cementing Design process, Gas Tight Slurry Cement would be applied.Based on the Casing Setting Depth analysis in the SYH-05 well drilling operation, there were 4 trajectories, namely: Conductor Casing 20”, 0-80m; Surface Casing 13-3/8”, 80-663.69m; Production Case 9-5/8”, 663.69-1060m; and Production Liner 7”, 1060.50-1694.65m. The implementation of Well Control was aimed to tackle the shallow gas kick was successfully executed in less than 1 hour without incident or accident. Work on the 17-1/2” trajectory which was a shallow gas zone could be done with the planned timetable.Keywords: Drilling hazard, Shallow gas kick, Optimization, Countermeasures